Methods and Characteristics of Quality Control of Composite Materials - Nuriddin, Sharipov; Farmanovich, Rajabov (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2025)
In modern industry, the demand for high-quality and reliable composite materials is increasing day by day. Ensuring the required operational properties of these materials directly depends on the methods and characteristics of their quality control. This article provides detailed information on the main and general directions of modernization programs adopted in our country, including the improvement of standard requirements, innovative, convenient, and at the same time high-performance methods of quality control and testing of composite materials. In particular, special attention is paid to the introduction of modern equipment and technologies, as well as the effective use of local raw materials and production capabilities[1,4]. Today, the development and improvement of non-destructive testing methods, precision measurement technologies, and automatic quality control systems for composite materials is becoming increasingly important. The use of ultrasonic, radiographic, thermal, optical, and electromagnetic control methods makes it possible to detect internal defects in materials, evaluate their physical and mechanical properties, and monitor the stability of technological processes. In addition, the introduction of digital technologies, artificial intelligence, and modern software complexes ensures the objectivity and accuracy of control results[2,3]. The article also analyzes international experience in ensuring the quality and reliability of composite materials, the role of certification and standardization processes, and the importance of creating regulatory frameworks adapted to the requirements of global markets. As a result, the formation of a comprehensive quality control system covering all stages — from raw material selection to final product testing — is of great importance in increasing the competitiveness of domestic composite materials and expanding their application fields